Markov Chain Scaffolding of Real World Data - Volchenkov, D. (Discontinuity, Nonlinearity, and Complexity, 2026)
Discrete time scale dependent random walks on a graph model of a relational database can be generated by a variety of equivalence relations imposed between walks (i.e.composite functions, inheritance, property relations, ancestor-descendant relations, data queries, address allocation and assignment polices). The Green function of diffusion process induce by the random walks allows to define scale dependent geometry. Geometric relations on databases can guide the datainterpretation. In particular, first passage times in a urban spatial network help to evaluate the tax assessment value of land.